Mengungkapkan Hubungan Antara Percaya Diri dan Kemampuan Pemecahan Masalah Matematis Siswa - Elmaini, Aldo; Wahyuni, Rika; Citroresmi P., Nindy (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to (1) determine the level of self-confidence among fourth-grade students at SDN 04 Singkawang in Mathematics lessons, (2) assess the level of mathematical problem-solving abilities of fourth-grade students at SDN 04 Singkawang, and (3) explore the relationship between self-confidence and mathematical problem-solving abilities among fourth-grade students at SDN 04 Singkawang. This research is quantitative in nature, employing a correlational study with a causal associative research design and using an asymmetrical relationship. The population of this study consists of all fourth-grade students, with the sample being the entire class, totaling 24 students. The results of the study are as follows: (1) The average self-confidence level of fourth-grade students at SDN 04 Singkawang is classified as "high," as evidenced by the percentage calculation, which reaches an average of 68.5. (2) The average test scores for mathematical problem-solving abilities of fourth-grade students at SDN 04 Singkawang are also classified as "high," demonstrated by the percentage calculation, which achieves an average of 74.1. (3) There is a significant relationship between self-confidence and mathematical problem-solving abilities among fourth-grade students at SDN 04 Singkawang. This result is indicated by a correlation test result of 0.881 < 0.05, with the category being "very high."